Embedded implementation research in programming at scale - the new normal to be! - Stefan Swartling Peterson (BMC, 2024)
Abstract If you want to run faster, don't just buy a new pair of shoes; also consider your training methods and where you run. This supplement examines six countries that have run faster than others in reducing under-five mortality, taking an implementation research approach, with country case studies done with local researchers and local institutions. Key generalizable learnings are to choose and adapt implementation strategies to context, design strategies to target the most vulnerable, systematically learn from implementation experience, and to leverage non-health-sector contributions. Embedding implementation research in programming has the potential to greatly improve and accelerate the contextualization and implementation of evidence-based child survival interventions to improve equity in coverage and overall effectiveness in reducing under-five mortality. It is now time to build such capacity in local institutions at scale, and incentives for concerned stakeholders to make this the new normal. Regional institutions should now take the lead in making this happen, not just in individual institutions and countries, but across entire regions, supported by global partners. Trial registration N/A.